Moving the people's economy through sustainable productive waqf in Jember regency from the perspective of maqashid al-syariah - Ulum, Bachrul; Saini, Saini; Muhammad, Izlawanie (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
Productive waqf is a waqf concept that not only functions as a donation for religious or social purposes, but is also managed professionally to generate profits that can be used for community empowerment. This research will examine how productive waqf management can make a real contribution to the local economy. Aspects to be studied include waqf asset management methods, economic sectors and long-term economic impacts resulting from the implementation of productive waqf from the perspective of maqashid al-syariah. Using a qualitative approach, this research will collect data from various sources, including interviews with waqf managers, community leaders, and waqf beneficiaries. Data analysis will be carried out to understand the dynamics and challenges faced in managing productive waqf and identify effective strategies to maximize the economic benefits of productive waqf. It is hoped that by adhering to the five main principles of religion (ad-din), soul (an-nafs), reason (al-'aql), descendants (an-nasl), and property (al-mal), which all work toward achieving community welfare, the study's findings will shed new light on the role of productive waqf as the primary tool in sustainable economic development in Jember Regency through the maqashid sharia approach. In this way, productive waqf also becomes a model of sustainable and inclusive economic development at the local level.